2018
DOI: 10.1039/c8ra01841c
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and hypolipidemic activities of eburicoic acid, a triterpenoid compound from Antrodia camphorata, by regulation of Akt phosphorylation, gluconeogenesis, and PPARα in streptozotocin-induced diabetic mice

Abstract: The study is designed to examine the potential effects and underlying mechanisms of eburicoic acid (TRR), a compound from Antrodia camphorata, in streptozotocin (STZ)-induced diabetic mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…Antcin K inhibits the fatty acid synthase, increases peroxisome α proliferator-activated receptor (PPAR-α) expression, and reduces the mRNA expression of sterol 1c regulatory element binding proteins (SREBP-1c) in the liver, thereby contributing to the decreased TAG levels and hepatic steatosis [57]. Similar results were obtained in the evaluation of eburicoic- [58] and dehydroeburicoic acids [59], two PTs obtained from Antrodia camphorata. There are various mechanisms potentially associated with TAG levels decreasing after SA exposition; the inhibition of human carboxylesterase type 1 (hCE1), an enzyme responsible of bulky alkyl chain ester such as TAGs, clearly related with obesity and T2DM progression [50].…”
Section: Biological Activity Assessmentsupporting
confidence: 57%
See 1 more Smart Citation
“…Antcin K inhibits the fatty acid synthase, increases peroxisome α proliferator-activated receptor (PPAR-α) expression, and reduces the mRNA expression of sterol 1c regulatory element binding proteins (SREBP-1c) in the liver, thereby contributing to the decreased TAG levels and hepatic steatosis [57]. Similar results were obtained in the evaluation of eburicoic- [58] and dehydroeburicoic acids [59], two PTs obtained from Antrodia camphorata. There are various mechanisms potentially associated with TAG levels decreasing after SA exposition; the inhibition of human carboxylesterase type 1 (hCE1), an enzyme responsible of bulky alkyl chain ester such as TAGs, clearly related with obesity and T2DM progression [50].…”
Section: Biological Activity Assessmentsupporting
confidence: 57%
“…Antcin K inhibits the fatty acid synthase, increases peroxisome α proliferator-activated receptor (PPAR-α) expression, and reduces the mRNA expression of sterol 1c regulatory element binding proteins (SREBP-1c) in the liver, thereby contributing to the decreased TAG levels and hepatic steatosis [57]. Similar results were obtained in the evaluation of eburicoic- [58] and dehydroeburicoic acids [59], two PTs obtained from Antrodia camphorata.…”
Section: Biological Activity Assessmentsupporting
confidence: 57%
“…Recently, compounds 1 and 2 were isolated from ACFB [ 30 , 37 , 38 , 39 ] and investigated for its reducing effects on blood glucose, total cholesterol, triglyceride and leptin levels in mice fed a high-fat diet (HFD) [ 30 ], as well as its antiproliferative activity [ 33 , 37 ] and inhibition against DEN-enhanced hepatocellular inflammation, fibrosis and carcinoma [ 38 ]. Compounds 3 , 7 and 8 were also obtained from ACFB [ 31 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 1 , 2 [ 30 ], 7 [ 28 ], and 8 [ 31 ] also showed hyperglycemic and antidiabetic properties via the glucose transporter 4 (GLUT4) and palmitate-treated C2C12 myotubes in mice fed a high-fat diet. Recently, compound 8 was investigated for its anti-type 1 diabetes and hypolipidemic activities [ 40 ]. However, potent aGI activity related to type 2 diabetes or obesity treatments had not been reported in the literature for all six active compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence has shown that the solid culture of the fruiting body and the filtrate in submerged culture have a hepatoprotective effect and antioxidant activity [4,5]. Our recent studies demonstrated that ergostatrien-3β-ol (EK100) [6], dehydroeburicoic acid (TR2), euricoic acid (TR1) [7,8,9,10], and antcin K [11] from A. cinnamomea exhibited antihyperglycemic and antihyperlipidemic activity. Nevertheless, the antidiabetic and antihyperlipidemic potential activities of sulphurenic acid (24-methylenelanosta-8-ene-3β,15α-diol-21-oic acid, 10; TR3; SA) (Figure 1) from A. camphorata remain unknown in streptozotocin (STZ)-induced diabetic mice.…”
Section: Introductionmentioning
confidence: 99%